SOSIALISASI PEMANFAATAN PERPUSTAKAAN DAERAH UNTUK MENINGKATKAN MINAT BACA SISWA DI DINAS PERPUSTAKAAN DAN KEARSIPAN KABUPATEN OKU TIMUR (Jurnal Pengabdian Kepada Masyarakat (ABDIMAS) Universitas Baturaja, 2023)
The more we read, the more information we get, such as reading in a library, the more knowledge we get. The library also acts as a liaison between sources of information and students whowant to develop their knowledge and experience. The library's efforts to increase students' readinginterest are carried out by strengthening the library's institutions. In general usage, the method is definedas a method or procedure used to achieve certain goals. Methods are defined as ways of presentinglearning materials to achieve the goals that have been set. Therefore, the skill of choosing a method issomething that must be mastered by the teacher. Of course, the selection of methods must be directlyrelated to the teacher's efforts in presenting lessons according to the situation and conditions so thatlearning objectives can be achieved optimally. By using this method, it is expected to increase students'reading interest in the regional archives and library services in the district. East OKU. The role of thelibrary in order to improve the quality of education, namely: fostering a love of reading, fosteringawareness of reading, and instilling reading habits among the educational community, guiding andaccelerating the mastery of reading techniques, expanding and deepening the learning experience, helpingthe development of language conversation and students' thinking power, fostering awareness to use andmaintain shared library materials, providing basic information retrieval capabilities.